Complete remission in PD-L1 high expression advanced gastric cancer patient with PD-L1 immunotherapy and chemotherapy integration treatment strategy: a case report - Yu, Xiaopeng; Zhao, Wenwen; Feng, Qingqing; Tian, Jin; Zhao, Lili; Xiao, Jun; Wei, Hongmei (Frontiers in Oncology, 2025)
Immune checkpoint inhibitors (ICIs) have become the standard of care in treating patients with human epidermal growth factor receptor 2(HER2) negative gastric cancer, revolutionizing the treatment landscape. The combination of ICIs and chemotherapy has shown improved treatment efficacy and prolonged survival compared to chemotherapy alone. Despite these benefits, this combined treatment is also linked to a higher incidence of adverse events. In this report, we present a case that demonstrates exceptional therapeutic efficacy but also severe adverse reactions. In HER2-negative gastric cancer, patients with higher programmed death-ligand1 (PD-L1) expression demonstrate improved clinical outcomes compared to those with lower PD-L1expression. This case study presents a 66-year-old male diagnosed with stage IV poorly differentiated gastric adenocarcinoma, characterized by hepatogastric ligament involvement, multiple peritoneal lymph node metastases, and extensive liver metastases. Initially treated with oxaliplatin plus docetaxel chemotherapy, the patient exhibited an inadequate response after two cycles. Subsequently, due to high PD-L1 expression, the treatment approach was modified to paclitaxel albumin-bound combined with oxaliplatin and Sintilimab. A PET-CT scan on June 5, 2023, confirmed complete remission in a patient with advanced gastric adenocarcinoma expressing high levels of PD-L1, who had received PD-L1-specific immune therapy in combination with chemotherapy. The patient developed frequent diarrhea three weeks after the final treatment on February 25, 2023, which was managed symptomatically. Tragically, the patient succumbed to electrolyte imbalance and shock caused by complications from the diarrhea in July 2023.